Tripartite organization of centromeric chromatin in budding yeast - Krassovsky, Kristina (National Academy of Sciences, 2012)
The centromere is the genetic locus that organizes the proteinaceous kinetochore and is responsible for attachment of the chromosome to the spindle at mitosis and meiosis. In most eukaryotes, the centromere consists of highly repetitive DNA sequences that are occupied by nucleosomes containing the CenH3 histone variant, whereas in budding yeast, a ∼120-bp centromere DNA element (CDE) that is sufficient for centromere function is occupied by a single right-handed histone variant CenH3 (Cse4) nucleosome. However, these in vivo observations are inconsistent with in vitro evidence for left-handed octameric CenH3 nucleosomes. To help resolve these inconsistencies, we characterized yeast centromeric chromatin at single base-pair resolution. Intact particles containing both Cse4 and H2A are precisely protected from micrococcal nuclease over the entire CDE of all 16 yeast centromeres in both solubilized chromatin and the insoluble kinetochore. Small DNA-binding proteins protect CDEI and CDEIII and delimit the centromeric nucleosome to the ∼80-bp CDEII, only enough for a single DNA wrap. As expected for a tripartite organization of centromeric chromatin, loss of Cbf1 protein, which binds to CDEI, both reduces the size of the centromere-protected region and shifts its location toward CDEIII. Surprisingly, Cse4 overproduction caused genome-wide misincorporation of nonfunctional CenH3-containing nucleosomes that protect ∼135 base pairs and are preferentially enriched at sites of high nucleosome turnover. Our detection of two forms of CenH3 nucleosomes in the yeast genome, a singly wrapped particle at the functional centromere and octamer-sized particles on chromosome arms, reconcile seemingly conflicting in vivo and in vitro observations.